Unity virtual reality projects : explore the world of virtual reality by building immersive and fun VR projects using Unity 3D - Linowes, Jonathan (Community experience distilled., 2015)
If you are a non-programmer unfamiliar with 3D computer graphics, or experienced in both but new to virtual reality, and are interested in building your own VR games or applications then this book is for you. Any experience in Unity is an advantage. Learn the basic principles of virtual reality applications and get to know how they differ from games and desktop apps. Build various types of VR experiences, including diorama, first-person characters, riding on rails, 360 degree projections, and social VR.